INVESTIGATION OF THE DISTRIBUTION OF DARK MATTER IN THE GALACTIC STRUCTURE - D. Kairatkyzy (Academic Scientific Journal of Computer Science, 2019)
We investigate the formation of disk-bulge-halo systems by including the basic components in the theory of the formation of galaxy. The purpose of this article is to investigate the distribution of dark matter in the Galactic structure and examine the impact of subhalo on the halo and the disk components to be included in one simple scenario of the formation of the galaxy. We investigate several important characteristics of galaxies, such as coordinates, position, velocity and masses, to form a stable component of the galaxy. We search for the parameters and physical processes that determine the subhalo-halo ratio, and thus largely explain the origin of the collision or other obstacles through the galactic halo. The spread over the radial velocities of the halo, combined with the spread of obstacles in the distances from the center of the galaxy, may explain the observed spread over the properties of the disk and the bulge. The paper uses data from Auriga_proper_unit - a data file of the main galaxies in Aurig-6 before free run. The units of data length used in Gadget2, such as coordinates and density, are converted from Mpc to kpc and also include star_age.